Mapping The Phenomenon Of Studentsâ Entrepreneurial Intention - Buana, Yud (Binus Business Review, 2016)
This research mapped the phenomena that occured in students who are taking classes entrepreneurship that was limited by entrepreneurial knowledge, personal attitude, social norms and self-efficacy. Using descriptive statistics on the answers of 794 respondents, who were students of Bina Nusantara University, produced a variety of results. Based on entrepreneurial knowledge, students still felt hesitant to be able to start and run the entrepreneurial process. On the other hand, self-efficacy and personal attitude reflect a positive thing associated, while the support of family and the environment around where they livevalued invariety. Although this research discovered phenomenon using all the attributes having impacts on entrepreneurship intention, potential students who are properly trained have a probability of playing a leading role in this regard. The benefits that can be expected from this research are useful in identifying suitable students for any entrepreneurial activity in the future with the support of educational institutions, families, and the government as a whole to form the atmosphere of an entrepreneurial culture.